A case study about acquisition of mechanically fixed cutting inserts - Daicu, Raluca; Diţu, Valentin; Oancea, Gheorghe (EDP Sciences, 2017)
During the process of turning metals there are used cutting inserts that can be acquisitioned from different producers. Because the offer is varied the acquisition must be made after an economical analysis that includes experimental tries. The paper presents an acquisition methodology for metallic carbide cutting inserts and presents a case study. This research was developed using three batches of cutting inserts acquisitioned from different producers. The specimen material was 1C45 and using the electrical current at cutting, the batches were analysed from qualitative and economical point of view.